Peritoneal Dialysis Catheter Placement by Open Surgical Technique: Nikdu Experience - Islam, Md Waliul; Alam, Kazi Shahnoor; Rashid, Md Mamunur; Rahman, Mohammad Mizanur; Hossain, Md Abul; sultana, Parveen (Bangladesh Journal of Urology, 2020)
Objective: To determine the outcome and complications of CAPD catheter implanted by open surgical technique for peritoneal dialysis. Methods: In this prospective study peritoneal dialysis catheter (PDC) for continuous ambulatory peritoneal dialysis was inserted into the abdominal cavity using an open surgical approach. We described our experience of open surgical minimal invasive technique of CAPD catheterization from July 2012 to June 2015. Total 40 catheters were inserted successfully. Patients were followed up for a variable period of 3-36 months. Results: In this study common indications of CAPD catheter insertion were CKD-5 due to diabetic nephropathy, chronic glomerulonephritis, and hypertensive nephrosclerosis. Common catheter related complications were peritonitis, hypokalaemia, exit site infection, catheter malfunction. Late peritonitis remains the major drawback of PD treatment, with the need of temporary or permanent changeover to the HD treatment in 10% of the patients. Conclusion: Enrichment of the physician’s interest and experience, along with a multidisciplinary approach to outline the optimal strategy of PD-catheter insertion and management of complications may improve technique and patients’ survival and decrease the morbidity. Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.62-67